Effects of Healthcare-Associated Infections on Length of PICU Stay and Mortality. Issue 11 (November 2019) - Hatachi, Takeshi; Inata, Yu; Moon, Kazue; Kawamura, Atsushi; Yoshida, Kota; Kinoshita, Makie; Shimizu, Yoshiyuki; Takeuchi, Muneyuki
Abstract : Objectives: To identify the effects of healthcare-associated infections on length of PICU stay and mortality. Design: Retrospective, single-center, observational study. Setting: PICU of a tertiary children's hospital. Patients: Consecutive patients who stayed greater than 48 hours in the PICU between January 2013 and December 2017. Interventions: None. Measurements and Main Results: Data were retrospectively collected from medical records. We identified occurrences of common healthcare-associated infections, including bloodstream infection, pneumonia, and urinary tract infection, defined according to the 2008 definitions of the Centers for Disease Control and Prevention and National Healthcare Safety Network. We assessed the effects of each healthcare-associated infection on length of PICU stay and PICU mortality using multivariable analysis. Among 1, 622 admissions with a PICU stay greater than 48 hours, the median age was 299 days and male patients comprised 51% of admissions. The primary diagnostic categories were cardiovascular (58% of admissions), respiratory (21%), gastrointestinal (8%), and neurologic/muscular (6%). The median length of PICU stay was 6 days, and the PICU mortality rate was 2.5%. A total of 167 healthcare-associated infections were identified, including 67 bloodstream infections (40%), 43 pneumonias (26%), and 57 urinary tract infections (34%). There were 152 admissions with at least one healthcare-associated infection (9.4% of admissions with a stay > 48 hr). On multivariable analysis, although each healthcare-associated infection was not significantly associated with mortality, bloodstream infection was associated with an extra length of PICU stay of 10.2 days (95% CI, 7.9–12.6 d), pneumonia 14.2 days (11.3–17.2 d), and urinary tract infection 6.5 days (4.0–9.0 d). Accordingly, 9.7% of patient-days were due to these three healthcare-associated infections among patients with a stay greater than 48 hours. Conclusions: Although healthcare-associated infections were not associated with PICU mortality, they were associated with extra length of PICU stay. As 9.7% of patient-days were due to healthcare-associated infections, robust prevention efforts are warranted.